2019
DOI: 10.1175/jpo-d-19-0070.1
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Layer Turbulence over Surface Waves in a Strongly Forced Condition: LES and Observation

Abstract: The impact of sea state on air–sea momentum flux (or wind stress) is a poorly understood component of wind–wave interactions, particularly in high wind conditions. The wind stress and mean wind profile over the ocean are influenced by the characteristics of boundary layer turbulence over surface waves, which are strongly modulated by transient airflow separation events; however, the features controlling their occurrence and intensity are not well known. A large-eddy simulation (LES) for wind over a sinusoidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(88 citation statements)
references
References 46 publications
5
83
0
Order By: Relevance
“…Babanin et al (2007) suggested that the growth rate should be enhanced to model the observed enhancement. However, Husain et al (2019) found that the wave growth rate actually decreases with wave steepness under strong wind forcing. This result is consistent with previous studies from the field (Donelan et al, 2006) and in the laboratory (Peirson & Garcia, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Babanin et al (2007) suggested that the growth rate should be enhanced to model the observed enhancement. However, Husain et al (2019) found that the wave growth rate actually decreases with wave steepness under strong wind forcing. This result is consistent with previous studies from the field (Donelan et al, 2006) and in the laboratory (Peirson & Garcia, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…All results are plotted using the full, O(ε 2 )-accurate expressions (A 57) and (A 58). The grey lines are the results for a fourth-order unforced Stokes wave, and the green dotted line represents ψ P = 3π/4 used in many of the other plots and supported by numerical simulations from Hara & Sullivan (2015) and Husain et al (2019). O(ε 2 )-accurate generalized Miles a 2 /(a 2 1 k) G (A 57) is also plotted in figures 3(b), 4(b) and 5(b).…”
Section: Harmonic Phase Relative Harmonic Amplitude and Wave Shapementioning
confidence: 90%
“…In the dynamic boundary condition (2.5), we incorporated the normal stress (surface pressure) but neglected the shear stress as it is usually significantly smaller than the normal stress (e.g. Kendall 1970;Hara & Sullivan 2015;Husain et al 2019). Additionally, we note that surface shear stresses cause a slight thickening of the boundary layer, which is equivalent to a pressure phase shift on the remainder of the water column (Longuet-Higgins 1969).…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of dependency of the exchange coefficients in MABL on wind speed is closely connected with the question of the influence of surface waves and spray, that is, the products of wind‐forcing on the exchange of the momentum and mass between the atmosphere and ocean. The effect of waves on the momentum transfer has been studied intensively (see, e.g., Ayet et al, 2020; Husain et al, 2019; Janssen, 1989; Makin et al, 1995; Makin & Mastenbroek, 1996; Makin & Kudryavtsev, 1999; Moon et al, 2004; Takagaki et al, 2012; Takagaki, Komori, & Suzuki, 2016; Takagaki, Komori, Suzuki, et al, 2016; Troitskaya et al, 2012, 2017; Troitskaya, Druzhinin, et al, 2018; Troitskaya, Kandaurov, et al, 2018; Troitskaya & Rybushkina, 2008, and references therein). It has been shown that the momentum transfer by wave disturbances, or the form drag, increases with increasing wind speed due to the widening of the wave spectra.…”
Section: Introductionmentioning
confidence: 99%